Cardio-respiratory Fitness in Medical Students by Queen’s College Step Test: A Cross-sectional Study - Koju, Bibek; Chaudhary, Shaligram; Joshi, Lok Raj; Shrestha, Anupama (Journal of Lumbini Medical College, 2019)
DOI: https://doi.org/10.22502/jlmc.7i1.268 Introduction: Cardio-respiratory fitness indicates the ability of circulatory system to supply oxygen to working muscles during continuous physical activity. Maximum oxygen uptake (VO2max) is a single best measure of cardio-respiratory fitness and is considered gold standard to quantify aerobic capacity. Methods: Eighty students of age group 18-25 years were taken by simple random sampling. VO2max was estimated indirectly by following the protocol of Queen’s College Step Test (QCST) method. Results: Mean value of VO2max for male (51.61±6.26 ml/Kg/min) and female (36.02±3.71 ml/Kg/min) was compared, which was found significantly higher in males than in females (p<0.001). There was negative correlation of gender (r = -0.838), body mass index (BMI) (r = -0.339), obesity category (r = -0.275), obese vs non-obese (r = -0.264) and basal pulse rate (r = -0.456) with VO2max and positive correlation of height (r = 0.592) and hours of study (r = 0.309) with VO2max. Conclusion: This study showed that increased BMI is associated with decreased level of VO2max in young adults. One can improve VO2max by maintaining BMI within normal limits.